Pembinaan Kurikulum Wajib Baca (KWB) untuk Mengoptimalisasi Digital Library “Lentera Ilmu” MI Baitussalam - Nurdianah, Lutfiyan (Khidmatuna: Jurnal Pengabdian Masyarakat, 2025)
The Digital Library "Lentera Ilmu" MI Baitussalam has several programs, where after further study, the programs carried out are more focused on solving problems in learning. However, the habituation stage of library visits as a source of many books is still not optimal. The habituation stage is still not maximized in the entire program in the digital library "Lentera Ilmu" MI Baitussalam. Librarians and teachers do not know and understand the compulsory reading curriculum program. Therefore, the service team carried out this activity to maximizing the digital library of the MI Baitussalam Lantern of Knowledge This activity was carried out during July-August 2023. The methods used to achieve the goals of service are conducting Focus Group Discussions (FGD) with related institutions and agencies, conducting socialization to teachers and librarians related to the Compulsory Reading Curriculum program, designing the Compulsory Reading Curriculum (KWB) program that is tailored to the circumstances of MI Baitussalam, conducting simulations of program implementation, evaluations and reports. Service activities are carried out systematically and receive quite high appreciation from the madrasah, as evidenced by the active participation of teachers and librarians during this service activity. The community service program has been carried out well and smoothly, and this service activity also produces a product, namely a reading track sheet with the title "Bacaanku Hari Ini" to monitor students' reading results and a compulsory reading curriculum guidebook that can be used by librarians and teachers in running the compulsory reading curriculum at school.